Dancing in the street : Motown and the cultural politics of Detroit - Smith, Suzanne E., 1964- (African American music reference., 1999)
"1960s Detroit was a city with a pulse: people were marching in step with Martin Luther King, Jr., dancing in the street with Martha and the Vandellas, facing off with city police. And through it all, Motown provided the beat. This book tells the story of Motown - as both musical style and entrepreneurial phenomenon - and of its intrinsic relationship to the politics and culture of Motor Town, USA."--Jacket